Influenza polymerase encoding mRNAs utilize atypical mRNA nuclear export - Larsen, Sean (BioMed Central, 2014)
BACKGROUND: Influenza is a segmented negative strand RNA virus. Each RNA segment is encapsulated by influenza nucleoprotein and bound by the viral RNA dependent RNA polymerase (RdRP) to form viral ribonucleoproteins responsible for RNA synthesis in the nucleus of the host cell. Influenza transcription results in spliced mRNAs (M2 and NS2), intron-containing mRNAs (M1 and NS1), and intron-less mRNAs (HA, NA, NP, PB1, PB2, and PA), all of which undergo nuclear export into the cytoplasm for translation. Most cellular mRNA nuclear export is Nxf1-mediated, while select mRNAs utilize Crm1. METHODS: Here we inhibited Nxf1 and Crm1 nuclear export prior to infection with influenza A/Udorn/307/1972(H3N2) virus and analyzed influenza intron-less mRNAs using cellular fractionation and reverse transcription - quantitative polymerase chain reaction (RT-qPCR). We examined direct interaction between Nxf1 and influenza intron-less mRNAs using immuno purification of Nxf1 and RT-PCR of associated RNA. RESULTS: Inhibition of Nxf1 resulted in less influenza intron-less mRNA export into the cytoplasm for HA and NA influenza mRNAs in both human embryonic kidney cell line (293 T) and human lung adenocarcinoma epithelial cell line (A549). However, in 293 T cells no change was observed for mRNAs encoding the components of the viral ribonucleoproteins; NP, PA, PB1, and PB2, while in A549 cells, only PA, PB1, and PB2 mRNAs, encoding the RdRP, remained unaffected; NP mRNA was reduced in the cytoplasm. In A549 cells NP, NA, HA, mRNAs were found associated with Nxf1 but PA, PB1, and PB2 mRNAs were not. Crm1 inhibition also resulted in no significant difference in PA, PB1, and PB2 mRNA nuclear export. CONCLUSIONS: These results further confirm Nxf1-mediated nuclear export is functional during the influenza life cycle and hijacked for select influenza mRNA nuclear export. We reveal a cell type difference for Nxf1-mediated nuclear export of influenza NP mRNA, a reminder that cell type can influence molecular mechanisms. Importantly, we conclude that in both A549 and 293 T cells, PA, PB1, and PB2 mRNA nuclear export is Nxf1 and Crm1 independent. Our data support the hypothesis that PA, PB1, and PB2 mRNAs, encoding the influenza RdRP, utilize atypical mRNA nuclear export.